A user guide to the CCAFS Gender and Climate Change Survey data - Bryan, Elizabeth; Bernier, Quinn; Ringler, Claudia; Meinzen-Dick, Ruth S.; Kovarik, Chiara; Haglund, Eric; Kristjanson, Patti; Mango, Joash; Herrero, Mario; Rufino, Mariana; Silvestri, Silvia; Quiros, Carlos; et al. (International Food Policy Research Institute, 2018)
The CCAFS Gender and Climate Survey data were collected in 4 sites in Africa South of the Sahara in early 2013 as part of the CGIAR Research Program on Climate Change Agriculture and Food Security (CCAFS) under the project on Increasing Women’s Resilience to Confront Climate Change.2 The survey grew out of collaboration, organized by CCAFS, between researchers participating in the program from the International Food Policy Research Institute (IFPRI) and the International Livestock Research Institute (ILRI). The project aimed to enhance understanding of gendered climate change perceptions, impacts, coping and adaptation strategies, and the constraints to adaptation within selected CCAFS baseline sites in Kenya, Senegal and Uganda. These issues are areas where CCAFS interventions may lead to gender transformative outcomes. Specifically, the survey was designed to answer the following questions: How do men and women perceive climate change and, particularly, the livelihood risks associated with climate change? What are the gender disparities in access to and control over assets and how and to what degree does the disparity in assets affect how men and women experience climate shocks and change? How and to what degree does asset disparity determine how men and women respond to climate shocks and change? Which coping strategies and adaptation options are favored by women and men, respectively, and why? The survey collected detailed gender-disaggregated data on these issues to inform strategies to increase climate change resilience among both women and men farmers. Multiple members of each household were surveyed to capture gendered views and experiences. The data, therefore, offer valuable insights into the ways in which men and women perceive and adopt innovations differently.